The anatomy murders : being the true and spectacular history of Edinburgh's notorious Burke and Hare, and of the man of science who abetted them in the commission of their most heinous crimes - Rosner, Lisa (EBL-Schweitzer, 2010)
This text situates the story of Burke and Hare against the social and cultural forces that were bringing early 19th-century Britain into modernity. Each of the murder victims provides a window on a different aspect of this world in transition.